Answer:
The solution to the system of equations is;
![\begin{gathered} x=1 \\ y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q0scsokjbpgjjax6m6ueamqn6l3y5kzdqd.png)
Step-by-step explanation:
Given the system of equation;
![\begin{gathered} y=5x-1\text{ ---------1} \\ 6x+2y=14\text{ ----------2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2n7kndwc5pici2erbesycct34v99q296u2.png)
Let us solve by substitution;
substitute equation 1 to 2;
![\begin{gathered} 6x+2(5x-1)=14 \\ 6x+10x-2=14 \\ 16x-2=14 \\ 16x=14+2 \\ 16x=16 \\ x=(16)/(16) \\ x=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h0jhy3l4olph9tq3hgzx7mtv7bs1ledgxv.png)
since we have the value of x, let us substitute into equation 1 to get the value of y;
![\begin{gathered} y=5x-1 \\ y=5(1)-1 \\ y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yh2lwmwb1rrdsoptqms3fwqgnu9x9wiavr.png)
Therefore, the solution to the system of equations is;
![\begin{gathered} x=1 \\ y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q0scsokjbpgjjax6m6ueamqn6l3y5kzdqd.png)